Co-movements of income and urbanization through energy use and pollution: An investigation for world’s leading polluting countries - Ramesh Chandra Das; Tonmoy Chatterjee; Enrico Ivaldi (Ecological Indicators, 2023)
Economic growth via urbanization helps in the accumulation of capital in the urban area. Again, to meet up the urban demand, energy consumption increases sharply, and consequently as the byproduct, magnitude of carbon emission also increases in the environment. The existing literature did not focus upon the high trajectory of carbon emission following urbanization. There is, thus, an interlink too between income growth and magnitudes of urbanization. Therefore, the co-movements between income and urbanization, and the connotation among income, urbanization, energy use and Green House Gas emissions are an area to be explored for the highly polluting nations. This study thus aims to investigate whether income, urbanization, energy uses and GHG emissions are cointegrated or having co-movements for the world’s top 20 polluting nations for the period 1970–2018. The study first underpins a theoretical background for the association among the four indicators and then goes for empirical verifications using time series econometric exercise. Using Johansen cointegration test and Vector Error Correction Model (VECM) for the variables the results show that the variables have long run associations as well as short run causal interplays in mostly the developed countries of the list. Income and urbanization have latent explanatory powers through energy use and GHG emissions. Hence, the policy makers of the concerned countries should focus on controlling the process of urbanization in order to manage energy use and GHG emissions to ultimately reach to the end of sustainable development.